The Influence of Fiber Treatment and Matrix Type on the Impregnation Quality of Carbon Fiber Reinforced Thermoplastics - Budiyantoro, Cahyo; Sosiati, Harini; Syahputra, Kevin Atila; Sudarisman, Sudarisman (Universitas Muhammadiyah Yogyakarta, 2023)
One of the main issues with Carbon Fiber Reinforced Thermoplastics (CFRTP) is the poor impregnation quality of the matrix on carbon fiber due to the high viscosity of the thermoplastic. Impregnation quality can significantly affect the mechanical properties of the composite. This study aims to compare the impregnation abilities of various types of thermoplastic matrices on carbon fiber. The matrices used in this study are HDPE, PC, and PET. Three variations of carbon fiber treatment were employed: the first variation involved immersion in liquid nitrogen at -196°C, the second variation included heating in an electric furnace at 600°C followed by rapid cooling in liquid nitrogen, and the third variation utilized treatment with a silane coupling agent. The research findings demonstrate that composites comprising a Polycarbonate matrix and carbon fiber reinforcement, treated with a silane coupling agent, exhibit superior impregnation quality, as evidenced by an Interfacial Shear Strength (IFSS) value of 9.34 MPa.. The lowest impregnation quality was observed in HDPE reinforced with carbon fiber that had been heated and rapidly cooled, with an IFSS of 5.52 MPa.